Partial albinism in Rhinelepis aspera from the Upper Parana Basin, Brazil, with a review of albinism in South American freshwater fishes - Nobile, Andre Batista [UNESP]; Freitas-Souza, Diogo [UNESP]; Lima, Felipe Pontieri de [UNESP]; Acosta, Aline Angelina [UNESP]; Da Silva, Reinaldo Jose [UNESP] (Inst Biologia, Univ Nacional Autonoma Mexico, 2016)
This study reports a case of partial albinism in Rhinelepis aspera from the Aguapei River, Upper Parana Basin, Brazil and provides a review of albinism cases in freshwater fishes from South America. The captured specimen has depigmentation throughout almost its entire body, with pigmented eyes and little dark spots on the dorsal and caudal fins. It is an adult male, and we suggest that due to the benthic habitat, it would be able to reach adult size, avoiding predators. The review shows a scarcity of this phenomenon in nature. All Rights Reserved (C) 2016 Universidad Nacional Autonoma de Mexico, Instituto de Biologia.
Keywords: Albinism; Leucism; Fish; Loricariidae